Morpho-cultural and molecular phylogenetic analyses reveal Neoarthrinium kaempferiae sp. nov. (Neoarthriniaceae), an endophytic fungus from Kaempferia galanga in Guangdong, China - Li, Yan-Xia; Doilom, Mingkwan; Dong, Wei; Liao, Chun-Fang; Phukhamsakda, Chayanard; Hongsanan, Sinang; Jayawardena, Ruvishika S.; Khongphinitbunjong, Kitiphong; Lin, Xin; Xu, Biao; Hyde, Kevin D. (Phytotaxa, 2026)
During an investigation of endophytic fungi associated with medicinal plants in Guangdong Province, China, a new species of Neoarthrinium was isolated from asymptomatic leaves of Kaempferia galanga (Zingiberaceae). The novel species, Neoarthrinium kaempferiae sp. nov., is introduced based on morphological characteristics and multi-locus phylogenetic analyses. It is characterized by smooth, cylindrical, ampulliform to subglobose conidiogenous cells, and globose to ellipsoidal, dark brown to black conidia that are mostly refractive blue in water mounts. Phylogenetic analyses of combined internal transcribed spacer (ITS), large subunit of ribosomal DNA (LSU), translation elongation factor 1-alpha (tef1-α), and β-tubulin (tub2) sequences support the taxonomic distinctness of N. kaempferiae from other species in the genus. This study represents the first record of Neoarthrinium species associated with Kaempferia galanga, expanding the known host range of this genus.